Effectiveness of breeding and disseminating CMDresistant cassava varieties in western Kenya - Abele, S.; Twine, Edgar E.; Ntawuruhunga, Pheneas; Tenywa, J.S.; Nampala, P.; Okori, Patrick; Kyamuhangire, W.; Adipala, E.; Tusiome, G.; Odendo, M.; Obiero, H.; Odenya, J. (2005)
In 1996, Cassava Mosaic Disease in Western Kenya depressed productivity and de-stabilized markets. The study assesses the effectiveness of breeding and disseminating CMD-resistant varieties in western Kenya by determining the extent of adoption and impact on farmers' income of the new varieties vis-àvis the level of investment in the program as well as the factors that influenced their adoption. Results show that the new varieties significantly increased production and marketing potential of cassava compared to the old varieties, despite the low level of investment in the breeding and dissemination system. This shows that the current cassava breeding and dissemination system is capable of reacting quickly and cost-effectively to CMD epidemics. However, an adoption rate of only 30 percent was realised. This was due to higher gains from competing crops like maize and beans in terms of cash income and productivity, and problems with the new varieties' attributes such as little drought resistance and long cropping cycles. High dry matter content, farm size, access to markets and information, among others, significantly influenced adoption, with farmer-to-farmer propaganda being the most efficient means of dissemination.